Isolated Small Bowel Transplantation in Turkey: A Single Center Experience Running Title: Isolated Small Bowel Transplantation in Turkey - Sert, Ismail; Kebabci, Eyup; Tugmen, Cem; Baran, Masallah; Dogan, Sait Murat; KÄ±lÄ±nc, Selcuk; Kose, IsÄ±l; Gunturk, Sanem; Soyoz, Mustafa; Olmez, Mustafa; et al. (European Scientific Journal, ESJ, 2016)
Background SBTx has become a feasible therapeutic option for patients with irreversible intestinal failure. Increase in the number and in the improvement of the patient and graft survival in SBTx has a slow course when compared to other solid organ transplantation. Aim The aim of this study is to analyze 25 isolated SBTx performed since 2003 at a single center. It also aims to compare the patient and graft survivals rate during the early (before 2010) and late (after 2010) period. Materials and Methods Medical charts of 24 patients were analyzed retrospectively. To compare the centerâ€™s experience during a twelve year period, the results were divided into two groups (before (n:7) and after 2010 (n:18)). At the appropriate time, data were reported as meanÂ± standard deviation, median, and range. Kaplan Meier method was used for the survival analysis of the graft and the patients. Results Median age of the patients was 39 (min 6 months, max: 56 yr). Six of them were in the pediatric age group. Compared to before 2010, graft survival rates increased from 28.1% to 53.8% in 3 months, from 28.6% to 35.9% in 6 months, and from 14.3% to 29.9% in one year after 2010. At the same period, patient survival rate increased from 57.1% to 72.2% in 3 months, from 28.6% to 38.9% in 6 months, and from 14.3% to 33.3% in one year. In the pediatric age group, patient and graft survival rates were 85.7% in 3 months, 71.4% in 6 months, and 71.4 % in 1 year. Conclusion SBTx is an effective treatment choice for selected patients with intestinal failure. Although patient and graft survival rates were improved after 2010 in our center, it was inferior. Patient and graft survival rates in pediatric SBTx are favourable and promising.